Stimulation of Reparative Regeneration of Articular Cartilage Under the Effect of Cord Blood Low Molecular Fraction (below 5 kDa) - Gulevsky, A. K.; Grischenko, V. I.; Ivanov, E. G. (Problems of Cryobiology and Cryomedicine, 2009)
There were studied the features of reparative regeneration of articular cartilage in rats under the effect of low molecular fraction (below 5 kDa), isolated from cord blood cryohemolysate and the reference substance â€œActoveginâ€. The peculiarities of biochemical composition of cartilage tissue under experimental conditions were established. Positive morphological change in cartilage tissue state was radiologically shown. The research performed demonstrated the normalisation of locomotor activity in rats to the 28th day of research.